Cannabis joint triggered recurrent anterior myocardial infarction in an adolescent taking dual anti-platelet therapy - Biyik, Ismail; Akturk, Ibrahim Faruk; Yalcin, Ahmet Arif; Tanidir, Ibrahim Cansaran; Erturk, Mehmet (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
Cannabis smoking has been rising world-wide especially in industrialized western countries. It has been known that cannabis use has adverse effects on the heart and vascular system and an increased risk of acute myocardial infarction (AMI) has been reported. The actual mechanism of cannabis-related AMI is not well known. In this report, we describe an adolescent with cannabis-induced recurrent left anterior descending coronary artery thrombosis and anterior myocardial infarction even on dual anti-platelet therapy.